Foliar pH, an emerging plant functional trait: Biogeography and variability across northern China. Issue 3 (28th December 2018) - Liu, Sining; Yan, Zhengbing; Chen, Yahan; Zhang, Meixia; Chen, Jiao; Han, Wenxuan
Abstract: Aims: Plant pH is a functional trait deserving more attention than the current few studies at local scales, given its roles in nutrient cycling and physiological processes. How plant pH varies and is regulated at large scales remain unclear. Here we explore the biogeography of foliar pH and the potential drivers. Location: East–west transect of northern China with increasing aridity westward. Time period: 2016–2017. Major taxa: Spermatophytes. Methods: We analysed foliar pH of plants from 22 sites across northern China, and investigated its spatial pattern and relationships with climate, soil, and plant functional type (PFT). Results: Foliar pH was generally acidic (5.33 ± .04) in northern China, showing distinct geographical variability: foliar pH decreased significantly westward at an average rate of 0.25 units per 10° longitude. Climate, soil and PFT explained 11, 17 and 59% of the variance in foliar pH, respectively. Foliar pH decreased (about 0.16) with mean annual precipitation (per 100 mm), soil stress coefficient (per 10%) and aridity index (per 0.14), but increased with mean annual temperature (per 2 °C). Across PFTs, herbs exhibited higher foliar pH than woody plants (6.0 vs. 4.9); gymnosperms relative to angiosperms had lower foliar pH (3.7 vs. 5.6); and monocotyledons showed higher foliar pH compared with dicotyledons (6.0 vs. 5.5). Main conclusions: This study provides the first comprehensive analysis of the evident pattern of foliar pH over a large spatial scale. Foliar pH is higher in warm‐arid northwestern relative to cold‐humid northeastern China and in later‐ than earlier‐evolved plants. Similar to leaf mineral elements, foliar‐pH biogeography is shaped by the joint effects of climate, soil and PFT; PFT and moisture are the most influential factors. Our findings provide a new impetus for understanding functional biogeography, and lay the groundwork for research on the linkage of foliar pH to ecological functions and macroevolutionary implications.